Assertive Behavior Development for Drug Abuse Prevention through Group Guidance Services - Putri Gusti Maulinsari; Diana Septi Purnama (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to determine one kind of student attitude that must be developed by students to avoid drug abuse, namely assertiveness. To develop assertiveness, counseling teachers/counselors can train them in group guidance services. This study used an experimental method with one group pre-test and post-test design, the sample used was students who have low scores on assertive behavior. Data were collected using a questionnaire assertive instrument with a Likert scale. This study contains the analysis using a statistical t-test. The results showed that the influence of group counseling services on assertive behavior for the prevention of drug abuse with t-count (7.043) t table (1.83) with = 0.05.